2017
DOI: 10.1038/s41598-017-00944-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Analysis Reveals a Distinct Metabolic Profile of Patients with Primary Biliary Cholangitis

Abstract: Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease associated with profound metabolic changes. The purpose of this study was to identify a distinctive metabolic signature from the training set with 29 PBC patients, 30 hepatitis B virus (HBV)-caused cirrhosis (HBC) and 41 healthy controls, and to validate the applicability and stability of the distinctive model from the validation set with 21 PBC patients, 7 autoimmune hepatitis (AIH) and 9 HBC. The sera were investigated using high resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
1
34
0
2
Order By: Relevance
“…Glucose set aside, the most noticeable differences were the presence of high citraconate in diabetic individuals, which were not detected in controls. This metabolite is an isomeric carboxylic acid, derived from citrate which is known to inhibit fumarate reduction (Vaidyanathan et al 2001 ; Hao et al 2017 ). As a consequence, this would slow down the rest of the Krebs cycle and therefore limit the use of acetylCoA to produce ATP (You et al 2016 ; Hao et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose set aside, the most noticeable differences were the presence of high citraconate in diabetic individuals, which were not detected in controls. This metabolite is an isomeric carboxylic acid, derived from citrate which is known to inhibit fumarate reduction (Vaidyanathan et al 2001 ; Hao et al 2017 ). As a consequence, this would slow down the rest of the Krebs cycle and therefore limit the use of acetylCoA to produce ATP (You et al 2016 ; Hao et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…This metabolite is an isomeric carboxylic acid, derived from citrate which is known to inhibit fumarate reduction (Vaidyanathan et al 2001 ; Hao et al 2017 ). As a consequence, this would slow down the rest of the Krebs cycle and therefore limit the use of acetylCoA to produce ATP (You et al 2016 ; Hao et al 2017 ). Eventually, excessive acetylCoA may be directed towards de novo lipid synthesis and contribute to lipid accumulation in the liver (Solinas et al 2015 ; Postic and Girard 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…In receiver operating characteristic (ROC) analysis, an impressive AUC of 0.937 for the training group was reported accompanied by an equally impressive 0.890 for the validation group making metabolomics a feasible diagnostic tool. 34 …”
Section: Biomarkers For Pbc Diagnosismentioning
confidence: 99%
“…Multiple metabolomic studies on HBV+ and HCV+ patients have been reported. For HBV, the studies mostly sought biomarkers of the development of cirrhosis or HCC [ 24 , 46 , 47 , 48 , 49 ] or biomarkers simply of HBV infection itself [ 10 , 28 ]. Similar studies have been reported in the case of HCV for serum biomarkers of progression to HCC [ 21 , 22 , 23 ] and for hepatic fibrosis [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%